PHYSIOLOGICAL CHARACTERISTICS RELATED TO CARBON SEQUESTRATION OF TREE SPECIES IN HIGHLAND FOREST ECOSYSTEM OF MOUNT HALIMUN-SALAK NATIONAL PARK - Nuril Hidayati; M. Mansur; Titi Juhaeti (Indonesian Journal of Forestry Research, 2012)
Biological diversity can have significant contribution to reduce the build-up of greenhouse gases in the atmosphere. The trees in a forest stand form an essential part in the functioning of the terrestrial biosphere, especially in the carbon cycle. Yet tree photosynthesis is far less studied than crop photosynthesis for several reasons: the large number of species; difficulty in measuring photosynthesis of entire trees or of forest stands. This research aims to assess the contribution of biological diversity in carbon sequestration by analyzing the physiological characteristics (photosynthesis, transpiration, stomatal conductance, leaf chlorophyll content) of species native to tropical highland forest ecosystem of Mount Halimun-Salak National Park. The results showed that there was a wide range of variation of CO2 assimilation rate between tree species. The overall CO2 absorption rate ranged 1.1913 - 31.3875 µmolm-2 s-1, the highest rate was reached by Lithocarpus sp. (pasang parengpeng) (31.3875 µmolm-2 s-1)followed by Litsea noronhae(huru lumlum) (21.5750 µmolm-2 s-1), Saurauia nudiflora (kilebo) (11.8175 µmolm-2 s-1), Vernonia arborea (hamirung) (6.7125 µmolm-2 s-1) and Litsea.sp. (huru bodas) (6.2725 µmolm2 s-1). The rate of CO assimilation was affected by incident radiation and thus the photon flux (Q leaf). Correlation between CO assimilation and Q leaf under certain environmental condition was considerably high. Incident radiation and Q leaf also affected stomatal conductance and thus rate of transpiration.